Case report: A lung squamous cell carcinoma patient with a rare EGFR G719X mutation and high PD-L1 expression showed a good response to anti-PD1 therapy - Zhu, Zhen-feng; Bao, Xu-xia; Shi, Hong-yan; Gu, Xi-xi (Frontiers in Oncology, 2024)
Lung cancer treatment has transitioned fully into the era of immunotherapy, yielding substantial improvements in survival rate for patients with advanced non-small cell lung cancer (NSCLC). In this report, we present a case featuring a rare epidermal growth factor receptor (EGFR) mutation accompanied by high programmed death-ligand 1 (PD-L1) expression, demonstrating remarkable therapeutic efficacy through a combination of immunotherapy and chemotherapy. A 77-year-old male with no family history of cancer suffered from upper abdominal pain for more than half months in August 2020 and was diagnosed with stage IV (cT3N3M1c) lung squamous cell carcinoma (LUSC) harboring both a rare EGFR p.G719C mutation and high expression of PD-L1 (tumor proportion score[TPS] = 9990%). Treatment with the second-generation targeted therapy drug Afatinib was initiated on September 25, 2020. However, resistance ensued after 1.5 months of treatment. On November 17, 2020, immunotherapy was combined with chemotherapy (Sintilimab + Albumin-bound paclitaxel + Cisplatin), and a CT scan conducted three months later revealed significant tumor regression with a favorable therapeutic effect. Subsequently, the patient received one year of maintenance therapy with Sintilimab, with follow-up CT scans demonstrating subtle tumor shrinkage (stable disease). This case provides evidence for the feasibility and efficacy of immunotherapy combined with chemotherapy in the treatment of EGFR-mutated and PD-L1 highly expressed LUSC.